Aspek Interoperabilitas Antara Lantamal IX Dengan Kamla Zona Bahari Timur Dalam Penegakan Hukum Di Laut Maluku Ditinjau Dari Perspektif Harmonisasi Hukum - Andrizal Andrizal; John Dirk Pasalbessy; Arman Anwar (Postgraduate Program in Law, Universitas Pattimura, 2021)
Introductioan: The basic conception of the realization of security in the territorial waters essentially has two dimensions, namely the enforcement of sovereignty and the enforcement of security which are interrelated with each other.Purposes of the Research: This study aims to analyze and discuss the interoperability between Lantamal IX and Kamla of the East Maritime Zone in law enforcement in the Maluku Sea is viewed from the perspective of legal harmonization and the obstacles faced by Lantamal IX and Kamla of the East Maritime Zone in Law Enforcement in the Maluku Sea when interoperability is connected. with efforts to harmonize the law.Methods of the Research: The research was conducted using a normative juridical method with a c statutory approach, conceptual approach and comparative approach a by specifically analyzing the performance of the institution and its authority in the implementation of law enforcement in the Maluku Sea based on the legislation which was then analyzed qualitatively.Results of the Research: The results showed that Lantamal IX and Kamla East Maritime Zone had the same authority in conducting security and safety patrols in the Maluku Sea, thus potentially causing overlapping authorities. Therefore, interoperability is needed between the two institutions in order to create synergy and minimize the occurrence of sectoral egos. So far, the interoperability of Lantamal IX and Kamla of the East Maritime Zone has been established, but it has not run optimally and continuously. Functional analysis of the collaboration between LANTAMAL IX and the East Maritime Zone Kamla shows that there are obstacles related to juridical and material aspects. In the juridical aspect, the East Maritime Zone Kamla does not have the authority to investigate so that the ship being considered must be handed over to the authorized agency. In addition, there has been no renewal of the memorandum of understanding between BAKAMLA and TNI Headquarters. As a result, patrol operations are not supported by Indonesian Navy warships. Meanwhile, materially, the facilities and infrastructure of the East Maritime Zone Kamla are minimal while BAKAMLA has a large enough budget for the implementation of operations. Likewise, the synergy of operations and sharing of data and information has not been maximized. Therefore, interoperability is needed through harmonization of law and synergy.